IMF Staff papers : Volume 24 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1977)
This paper is an attempt to examine several theories about the dynamics of exchange rate adjustment. All the models start from the premise that exchange rates are determined by the balancing of supply and demand for each currency and that expectations play a prime role in determining demand. The paper considers four aspects of the exchange rate adjustment process-each of which has been proposed as a source of exchange rate variability. First, the long-standing debate on stabilizing versus destabilizing speculation is re-examined. Possible patterns of exchange rate movements that might result from both extrapolative and rational expectations are shown. Then, the assumptions and exchange rate adjustment pattern implied by the asset market equilibrium approach to exchange rate determination are described. No one aspect of the exchange rate adjustment considered in this paper is held to be responsible for the large exchange rate variations observed in recent years. Rather, from both an a priori consideration and empirical examinations, each of the processes considered appears to have contributed to observed exchange rate variations.